Regulating Foreign Direct Investment for Development Perspectives from Bangladesh - Nasrullah, Nakib Mohammad (Routledge Focus on Environment and Sustainability Series, 2024)
This book offers an overview of the relationship between Foreign Direct Investment (FDI) regulation and sustainable development in Bangladesh. For researchers, students, and academics of economics, politics, sustainable development and economic growth. Also FDI strategists, policymakers, negotiators, administrators, and legislators